Implementation of Relationships between Stake holders in Small Scale Broiler Business Partnerships in Indonesia - Nyak Ilham (Indonesian Center for Animal Research and Development, 2020)
The problem of small-scale broiler business is the low efficiency and low application of biosecurity. In the chicken industry, however, efficiency is an essential consideration for product competitiveness in terms of both price and quality. Vertical integration involving small scale businesses in partnership models is expected to maintain the existence of small scale businesses. This paper aims to analyze the performance of the implementation of various models of broiler business partnerships with the legal basis for the establishment of partnership. In this paper there are four models to be discussed, namely: Partnership of National Price Contract (KKHN), Partnership of Regional Price Contracts (KKHR), Partnership of Local Broiler Maklun (KMLB), and Partnership of Local Revenue Sharing (KBHL). The implementation of legislation for the broiler partnership is weak. This can be seen from the tendency of the core companies to narrow down to the KKHN model, while other models are being pushed and bankrupt, and there is the occurrence of unilateral business relationship termination by the nucleus company to plasma as its business partner. The policy recommendations offered are: (i) There is a need to strengthen regulation and guidance by relevant agencies in charge of animal husbandry and animal health functions at the central and regional levels supported by Business Competition Supervision Commission (KPPU); (ii) The company is advised not to break the partnership relationship with small-scale farmers who have worked together for a long time; (iii) The company should reserve funds from the farmer's chicken harvest to reinvest the chicken cage.